Antisocial personality disorder and Dark Tetrad personality traits, violent crime, and recidivism : A systematic review - Rawatlal, Nishola (University of Pretoria, 2021)
Mini Dissertation (MA (Clinical Psychology))--University of Pretoria, 2021.